Fabrication of a Microtubular La0.6Sr0.4Ti0.2Fe0.8O3−δ Membrane by Electrophoretic Deposition for Hydrogen Production - Kyoung-Jin Lee; Yeong-Ju Choe; Jun-Sung Lee; Hae-Jin Hwang (Advances in Materials Science and Engineering)
Microtubular type La0.6Sr0.4Ti0.2Fe0.8O3−δ (LSTF) membranes were prepared by electrophoretic deposition (EPD). The oxygen permeation and hydrogen production behavior of the membranes were investigated under various conditions. LSTF green layer was successfully coated onto a carbon rod and, after heat treatment at 1400°C in air, a dense LSTF tubular membrane with a thickness of 250 mm can be obtained. The oxygen permeation and hydrogen production rate were enhanced by CH4 in the permeate side, and the hydrogen production rate by water splitting was 0.22 mL/min·cm2 at 1000°C. It is believed that hydrogen production via water splitting using these tubular LSTF membranes is possible.